EFEKTIVITAS SERBUK DAUN TANAMAN KAYU MANIS (Cinnamomum burmanii) TERHADAP DIFERENSIAL LEUKOSIT DAN AKTIVITAS FAGOSITOSIS IKAN NILA (Oreochoromis niloticus) YANG DIINFEKSI Streptococcus agalactiae - Sri Wulandari; Rahmad Jumadi; Firma Fika Rahmawati (Universitas Muhammadiyah Gresik, 2018)
The main problem in the cultivation of tilapia is the attack of bacterial disease Streptococcosiscaused by Streptococcus agalactiae bacteria. Alternative measures to prevent the disease ofStreptocococis can be through the use of phytopharmaca materials. One of the ingredients ofphytopharmaca can be used is cinnamon plant. Cinnamon leaves contain several types of activesubstances such as tannins, eugenol, safrole, calcium oxalate, resin, saponins, tanners, andsinamaldehid. The objective of the study of effectiveness of leaf powder of cinnamon plant toleukocyte differential and phagocytic activity in tilapia (Oreochromis niloticus) infected byStreptococcus agalactiae is to know the influence and dosage of cinnamon leaf powder in feedtoLeukocyte Differentiation and Phagocytosis Activity Postcainfection Streptococcus agalactiaein tilapia (Oreochromis niloticus). This research used 3treatment 4 replication and control withdose K- = challenge test, K+ = without test challenge, A = dose 0,25%, B = dose 0,5%, C = 1%.The parameters observed are Leukocyte Differential and Phagocytosis Activity. Dosage 0.5%addition of leaf powder cinnamon plant on feed is the best dose. Giving of cinnamon leaf powderin feed influenced to increase of leukocyte difference especially on monocyte cell and neutrophilcell was significantly different (P>0,05) than K+ without addition of cinnamon leaf powderwhile phagocytic activity had an effect on Streptococcus agacatiae.